EFL Teachers’ Mindfulness and Emotion Regulation in Language Context - Wang, Na (Frontiers in Psychology, 2022)
The academic setting is a collection of diverse emotive needs that require skillful educators who can regulate and deal with them. Emotion regulation by language educators emphasizes the techniques that language educators use to regulate their emotions. In addition, English as a Foreign Language (EFL) teachers have a growing interest in examining the utilization of mindfulness-based methods to study and instruct a foreign language. Indeed, it is regarded as a strategy that has been connected to constructive encouragement when utilized as a managing technique for anxiety and worry. Concerning this, the goal of this mini review is to examine the function of mindfulness in regulating educators’ focus, emotion, manner, and contemplation. Some theoretical suggestions for educational situations are presented.